2017
DOI: 10.1161/circinterventions.116.004848
|View full text |Cite
|
Sign up to set email alerts
|

Directional Atherectomy Followed by a Paclitaxel-Coated Balloon to Inhibit Restenosis and Maintain Vessel Patency

Abstract: Background—Studies assessing drug-coated balloons (DCB) for the treatment of femoropopliteal artery disease are encouraging. However, challenging lesions, such as severely calcified, remain difficult to treat with DCB alone. Vessel preparation with directional atherectomy (DA) potentially improves outcomes of DCB.Methods and Results—DEFINITIVE AR study (Directional Atherectomy Followed by a Paclitaxel-Coated Balloon to Inhibit Restenosis and Maintain Vessel Patency—A Pilot Study of Anti-Restenosis Treatment) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
133
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 206 publications
(143 citation statements)
references
References 25 publications
6
133
0
4
Order By: Relevance
“…Also, no differences in CD‐TLR were noted in patients with calcific atherosclerosis with unusual, very low CD‐TLR across all patient and lesion cohorts. Calcium burden has been demonstrated to impact clinical results with DCB, and vessel preparation to ablate this calcium may improve results particularly in longer lesions . Our current data supports further investigation with debulking of calcific lesions with the B‐Laser™ technology prior to arterial drug delivery.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Also, no differences in CD‐TLR were noted in patients with calcific atherosclerosis with unusual, very low CD‐TLR across all patient and lesion cohorts. Calcium burden has been demonstrated to impact clinical results with DCB, and vessel preparation to ablate this calcium may improve results particularly in longer lesions . Our current data supports further investigation with debulking of calcific lesions with the B‐Laser™ technology prior to arterial drug delivery.…”
Section: Discussionsupporting
confidence: 68%
“…Predefined secondary endpoints included ≤30% final residual diameter stenosis (including any adjunctive therapy), with no flow limiting dissection; Freedom from perioperative and up to 30 days device related complications in the target vessel (defined as perforation, dissection, distal embolization, in‐situ thrombus or pseudo‐aneurysm); as well as clinical outcome at 30 days and 6 months compared to baseline, as assessed by WIQ, ABI, Rutherford and duplex ultrasound patency (PSVR < 2.5). All angiographic cines and duplex films were evaluated by the respective core laboratories for the respective endpoints and all endpoints adverse events were adjudicated by CEC.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with conventional paclitaxel-coated stents, paclitaxel elution balloons show major advantages. High liposolubility indicates that paclitaxel is more suitable than other drugs for balloon coating: the paclitaxel on the surface of a balloon can be rapidly taken up by local vascular cells for drug transfer at the time of balloon expansion, which continuously inhibits the proliferation and migration of vascular smooth muscle cells [46,47]. Among various paclitaxel elution balloon products, the most representative are Braun SeQuent®Please balloons (Germany); the anti-restenosis effect of these products has been proven by a series of studies [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the DEFINITIVE AR trial (Determination of EFfectiveness of the SilverHawk_ PerIpheral Plaque ExcisioN System (SIlver‐HawkDevice) for the Treatment of Infrainguinal VEssels Antirestenosis) evaluated the use of DA + DCB (Bayer Healthcare's Paccocath®) or DCB alone in 100 patients with lesions between 7 and 15 cm. The trial showed no difference between the two groups with respect to 1‐year CD‐TLR (7.3% for DA + DCB vs. 8.0% for DCB alone) and patency as assessed by DUS (84.6% for DA + DCB vs. 81.3% for DCB alone) .…”
Section: Methodsmentioning
confidence: 92%